Bali Governor Regulation Number 47 of 2019 Concering The Authority of The Denpasar City Government in Waste Management - Yusuf, Dedi; Rahmasari, Betha (Universitas Muhammadiyah Metro, 2025)
The Bali Governor's Decree No. 381/03-P/HK/2021 and the Governor's Instruction No. 8324 of 2021 regarding Source-Based Waste Management are follow-up steps to the Governor's Regulation No. 47 of 2019. This policy aims to support the vision of